Multiplicity-dependent inclusive J/[psi] production at forward rapidity in pp collisions at √s=13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Menzel, Marius; Nath, Abhishek; et al. (Journal of high energy physics, 2025)
This paper presents a study of the inclusive forward J/ψ yield as a function of forward charged-particle multiplicity in pp collisions at √s = 13 TeV using data collected by the ALICE experiment at the CERN LHC. The results are presented in terms of relative J/ψ yields and relative charged-particle multiplicities with respect to these quantities obtained in inelastic collisions having at least one charged particle in the pseudorapidity range |η| < 1. The J/ψ mesons are reconstructed via their decay into μ+μ− pairs in the forward rapidity region (2.5 < y < 4). The relative multiplicity is estimated in the forward pseudorapidity range which overlaps with the J/ψ rapidity region. The results show a steeper-than-linear increase of the J/ψ yields versus the multiplicity. They are compared with previous measurements and theoretical model calculations.